Estrutura, conduta e governança na cadeia produtiva do leite: um estudo multicaso no Rio Grande do Sul - Breitenbach, Raquel (2012)
This thesis aimed to identify and analyze, in different regions of the state of Rio Grande do Sul, Brazil, which are and have evolved the market structures of raw milk, and what the implications on the behavior of economic agents (producers and industries) and on the coordination of the dairy production chain. The project used two research methods in successive steps. First, a survey was made of the existing market structures in different dairy production in Rio Grande do Sul, based on the number of processing industries. From this survey, revealing cases were identified that represented contrasts with each other and in relation to previous studies by the author for further development and achievement of specific objectives of the work. Data were analyzed based on framework proposed by the author, in which assumed that the market structures have an influence on the behavior of economic agents, and it brings effects to the entire production chain. The primary effects that are intended to identify and assess, refer to the chain configuration in relation to the transaction, namely, effects on the type and coordination mechanisms. Of these, it was assumed that the course could spin on the investments, the adoption of technological innovations and the remuneration of the activity, which were also the subject of analysis. As results, one can identify two different market structures factors in milk production chain in Rio Grande do Sul: the competitive oligopsony and monopsony. Given this identification, it showed a direct relationship between market structures and conduct of agents and governance structures. In competitive environments oligopsony, governance is predominantly hybrid, but with similar characteristics to the market, as well as for increased investment in dairy farming by farmers. Already in environments monopsony, governance Hybrid was also found, but with attributes rank and lower investment activity by providers.